The Effect of UMP Phantom Antenatal Care (ANC) Innovation on Leopold Examination Knowledge and Skills in Students at SMK Muhammadiyah 3 Purwokerto - Risya Rosyiana; Happy Dwi Aprilina (UM Purwokerto Press, 2024)
Background: Knowledge and skills are competencies that Nursing Assistant Vocational High School students must possess to create competent graduates. One of those knowledge and skills is the Antenatal Care (ANC) examination. The inadequate facilities and infrastructure at SMK can disrupt the learning process. The application of learning media can influence the learning process. The limited number of teaching aids can be an inhibiting factor in practical learning. The phantom innovation of antenatal care is a visual aid that resembles the body shape of pregnant women used for Leopold examinations. Method: The research method used Quasi Experiment using a posttest-only control group design approach. The population in this study were students of nursing assistants in XI and XII Grades at SMK Muhammadiyah 3 Purwokerto. The sample in this study amounted to 52 people. The sampling technique used was the total sampling technique. The data analysis used was univariate and bivariate analysis with the Mann-Whitney test. Results: The results showed that there is an influence of the Phantom ANC UMP innovation on the respondents Leopold examination knowledge and skills obtained from statistical test result the asymp sig value. (2-tailed) knowledge 0.00 and asymp value sig. (2-tailed) skill 0.01 which means the p value <0.05. Conclusion: The student's knowledge and skills regarding Leopold's examination were higher in the group using Phantom ANC UMP media than in the group using powerpoint media.